Pengaruh Media Pembelajaran Berbasis TPACK terhadap Kemampuan Menulis Teks Negosiasi Siswa Kelas X SMA Negeri 1 Cigemblong (Journal on Education, 2026)
This study aims to determine the effect of TPACK-based learning media focused on the use of the Vistacreate application on the ability to write negotiation texts of class X students of SMA Negeri Cigemblong in the 2025/2026 academic year. This study uses a quantitative approach using a quasi-experimental method. The data collection technique uses a pre-test and post-test in learning. The data analysis technique uses a normality test, a homogeneity test and a t-test. The results of the post-test calculation using the Vistacreate application obtained a Mean (????̅) = 79.33, Median (Me) = 80.00, Variant = 42.538 and standard deviation = 6.522. While for the post-test value of the control class using the Picsart application, namely, Mean (????̅) = 68.15, Median = 70.00, Variant = 73.746 and standard deviation = 8.588. Based on the data above, it can be concluded that the Vistacreate application as a learning media is considered good, while the Picsart application as a learning media is considered adequate. The results of the data above indicate a positive effect of the Vistacreate application on the negotiation text writing skills of 10th-grade students at SMA Negeri 1 Cigemblong.